Characterization of copper based chitosan nanoparticles synthesis by chemical method: Approach cytotoxic effects on MCF-7 cells - Fadhil , Ashwaq Abbass; Ahmed, Mais Emad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Chitosan polymer is an essential supporting material for the synthesis of metallic nanoparticles (MNPs) because of its exceptional capping and stabilizing qualities, biocompatibility, biodegradability, eco-friendliness, polycationicity, and non-toxicity. To produce copper-based chitosan nanoparticles, choose a suitable chemical procedure hydrothermal method. Each approach offers advantages in terms of homogeneity, morphology, and particle size. This study has produced, described, and examined the bacteriological characteristics of metal nanoparticles based on chitosan, including copper nanoparticles (CS-Cu NPs). Chitosan-based metal nanoparticles have been created using the solution casting technique. The generated nanoparticles were characterized using FTIR, AFM, UV, ZP, and SEM examination. The TEM image illustrates that the materials created are nanomaterials, ranging in size from 1 to 100 nm. The CS-CuNPs, displaying a stable brick-red hue, showed an absorption peak at 214 nm, indicative of monodisperse nanoparticle formation and surface plasmon resonance. X-ray diffraction confirmed the face-centered cubic structure with peaks at 36.78°, 43.38°, 50.56°, and 74.26°, and an average particle size by AFM to 62.45 nm. FTIR analysis showed interactions between chitosan and copper, particularly around 3370 –3226 cm⁻¹, 1633 cm⁻¹, and 680 cm⁻¹ and.The MCF7 cell line demonstrated the strongest anti-human breast cancer cell line properties of the nanocomposite when compared to the aforementioned cell lines. The aforementioned results suggest that the nanocomposite could be used to treat various forms of human breast cancer. Breast cancer had increased nanoparticle sensitivity. At a concentration of 25 μL/mL, Chi-Cu NPs demonstrated excellent cytotoxicity and anticancer activity, making them suitable for use as an anticancer agent.